y=5ln(2x-3)

Simple and best practice solution for y=5ln(2x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=5ln(2x-3) equation:


Simplifying
y = 5ln(2x + -3)

Reorder the terms:
y = 5ln(-3 + 2x)
y = (-3 * 5ln + 2x * 5ln)
y = (-15ln + 10lnx)

Solving
y = -15ln + 10lnx

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Simplifying
y = -15ln + 10lnx

See similar equations:

| -5(x+1)-17=11+2 | | 4t+3t-8=34 | | 8(3n+3)=6(7n+1)+3 | | 6(7x-8)=18x | | 12+6w=228 | | -4a=a+32 | | -3(1+6)=14-x | | -4(-2-3x)=13x | | 12+6w= | | 2(3x+5)=-4(x+4) | | 3(2n+3)=(7n+6)+2 | | -2-9=3x+7-2x | | 27n+36=14n+56+4 | | 3(2n+5)=6(8n+4)+6 | | 3w-8w=25 | | -3(-4-6y)+7(-y+15)=-8 | | 205x+55(10-x)=1000 | | tn=n+11 | | -3(6y-4)-y=-2(y-5) | | 3x+2x-x=8+3x-6 | | 9x^3+15x^2-6x= | | (3m-2)(2m+3)= | | 5(y-4)=7y-20 | | 7(8x-4)=60x | | -36-9x=-5x | | 50=2(9)+2W | | 26-9k=8k | | 8y+2(y-9)=5(y+1)-2 | | 6b-2=14 | | 7x=8(x+6)-7 | | m=70+t(a+b)forb | | -(8-x)-2(2x+4)-12x=-2 |

Equations solver categories